Impact of belt and road initiative (BRI) towards debt sustainability of BRI recipient countries - Hoong, Joana; Chan, Kelly Yun Jie; Low, Ke Mei; Yeoh, Yi Neng (2024)
The Belt and Road Initiative (BRI) has sparked widespread debates, with concerns raised regarding its potential to foster debt trap diplomacy. This study delves into the apprehensions surrounding the BRI-induced debt issues in Asia and empirically investigates the matter. By examining the debt levels of nine Asian countries post the BRI's initiation, employing the Panel Mean Group Autoregressive Distributed Lag (PMG-ARDL) model, this research assesses the short and long-term effects of the BRI on debt sustainability. Utilizing historical data spanning from 2003 to 2022, our findings reveal a nuanced picture. In the long run, the BRI demonstrates a significant tendency to reduce the government debt-to-GDP ratio. However, in the short run, outcomes vary across countries. Notably, Malaysia and Bangladesh exhibit a positive and significant impact, while Nepal experiences a considerable negative effect. This disparity underscores the influence of governmental efficacy on short-term outcomes. Consequently, our study advocates for the implementation of transparent and accountable governance mechanisms to ensure the efficient allocation of BRI funds. Such measures hold the potential to leverage the BRI for bolstering economic prospects in participating countries